2018
DOI: 10.1016/j.apgeochem.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Zinc isotopes as tracers of anthropogenic sources and biogeochemical processes in contaminated mangroves

Abstract: Recent work has shown that variations in zinc (Zn) isotope ratios enable us to identify contamination sources in the terrestrial environment and uptake processes in higher plants. Here in this study, we demonstrate that this also holds true for mangrove forests, which play an important role in the biogeochemical cycling of metals in tropical coastal ecosystems and that are seriously threatened by anthropogenic pollution. To this end, we determined zinc concentration and isotope composition (expressed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…This trend can be interpreted as a binary mixing process between Zn derived from terrigenous material and multiple anthropogenic Zn sources. Since sediment particle transport from rivers to oceans does not alter significantly Zn isotope compositions of the particulate phase (Araújo et al, 2018;Guinoiseau et al, 2018), isotope ratios in the suspended sediments behave conservatively, reflecting the relative Zn contributions of natural and anthropogenic sources.…”
Section: Identifying Anthropogenic and Natural Sources Using Cu And Zmentioning
confidence: 99%
“…This trend can be interpreted as a binary mixing process between Zn derived from terrigenous material and multiple anthropogenic Zn sources. Since sediment particle transport from rivers to oceans does not alter significantly Zn isotope compositions of the particulate phase (Araújo et al, 2018;Guinoiseau et al, 2018), isotope ratios in the suspended sediments behave conservatively, reflecting the relative Zn contributions of natural and anthropogenic sources.…”
Section: Identifying Anthropogenic and Natural Sources Using Cu And Zmentioning
confidence: 99%
“…2017), Zn (Araújo et al . 2017a, 2018, Desaulty and Petelet‐Giraud 2020) and Pb (Jeong et al . 2018, Nazarpour et al .…”
mentioning
confidence: 99%
“…3). Most of the sediments and SPM taken from lakes and rivers with little human impact ([Zn]particulate ≤ 200 mg/kg) have Zn isotope compositions varying from δ 66/64 Zn=+0.14 to +0.32‰ (n= 129, IQR, Araújo et al, 2017aAraújo et al, , 2017bAraújo et al, , 2019Araújo et al, , 2018Chen et al, 2009b;Guinoiseau et al, 2018Guinoiseau et al, , 2017Petit et al, 2015Petit et al, , 2008Sivry et al, 2008;Thapalia et al, 2010Thapalia et al, , 2015 this study) (Fig. S2).…”
Section: Natural Watermentioning
confidence: 99%
“…In their studies in the Sepetiba Bay (Brazil), Araújo et al (2018Araújo et al ( , 2017aAraújo et al ( , 2017b used Zn isotope compositions for core samples of stream sediments and SPM to reconstitute a timeline for changes in zinc contamination related to industrial metallurgy. From studying core samples of stream sediment, Sivry et al (2008) and Petit et al (2015) have also shown how zinc ore-smelter activity affects the river Lot's watershed (France).…”
Section: Rivers Impacted By Industrial Activitymentioning
confidence: 99%